Pomological traits and profitability of selected velvet apple germplasm - Sharif , M S; Robbani, M; Howlader, P; Rahman , M Z; Imran, M (Bangladesh Journal of Agriculture, 2023)
The research was accomplished during February to August, 2021 at Germplasm Center (GC), Patuakhali Science and Technology University (PSTU) and farmers’ homesteads in Patuakhali district to find out different characteristics, fruit yield and profitability of four velvet apple germplasm. The experiment was laid out in Randomized Complete Block Design (RCBD) with four replications. Results manifested that there were significant variations among the germplasm, where local red germplasm exhibited the highest plant height (5.54 m), plant diameter (16.23 cm), number of main branches (12.75), length of the largest branch (3.89 m), plant canopy (8.80 m2), leaf area (135.24 cm2) but those traits were minimum in PSTU Bilati gab-2. PSTU Bilati gab-2 emerged floral bud for the longest duration (32.25 days). The measured length of inflorescence before first flowering varied from 5.03 – 6.60 cm where it required 24 – 28.25 days for development. A range of flowers per inflorescence (7.75 – 11) and duration of flowering (46.5 – 59.25 days) were observed in all the studied germplasm. The percentage of fruit set (18.28 – 30.81) per plant with individual fruit weight 126.70 to 202.43 g. The highest pulp weight (103.85 g) was obtained from PSTU Bilati gab-2 and the lowest (69.25 g) from local yellow germplasm. PSTU Bilati gab-2 was completely seedless. So, it contained the highest edible portion (81.92%). The highest fruit yield (3.5 t/ha) was recorded in PSTU Bilati gab-1 but maximum net profit (251160 Tk/ha) was obtained from PSTU Bilati gab-2 with the highest benefit cost ratio (BCR) of 3.81. Considering percent fruit set, percent edible portion, fruit yield and profitability, PSTU Bilati gab-2 was found to be the best among the four germplasm. Bangladesh J. Agri. 2023, 48(2): 1-12